POLA RESPON MAHASISWA IAIN SALATIGA TERHADAP INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) - Winarno Winarno (IAIN Salatiga, 2016)
Information and communication technology that is now developing to give effect to the learning process. There is a change in the learning process, which is usually done limited learning in the classroom with a predetermined schedule developed into a distance learning can be done anywhere and anytime. Lessons usually involve facilities in the form of material like a book but now growing by utilizing the network (network) by using a computer with internet technology, thus forming pembelajaraan